History of Ancient Greece in Fifty Lives. - Stuttard, David (Thames and Hudson Ltd, 2014)
The political leaders, writers, artists and philosophers of ancient Greece turned a few city states into a pan-Mediterranean civilization. But who were these people, what do we know of their lives and how did they interact with one another? This highly readable, original new approach to telling the history of Greece weaves together the lives of the movers and shakers of the Greek world into a continuous narrative up until the rise of Rome. From mathematics to politics, from painting and sculpture to sport, the reader will meet both the famous and less well-known figures such as Milo, the Oly.